Sexual and reproductive health services according to adolescents boys (Bucaramanga, Colombia) - Elvinia Pinilla G; Clara M. Forero B; MaríaC. Valdivieso C; Luis C. Orozco V; Carlos Ardila; Lorena Gómez; Sandra León; Cecilia Velandia (Universidad de Antioquia, 2009)
Adolescents face different dilemmas, which may happen tobe not timely solved, pose major risks to health. Objective:To characterize the basic needs and expectations of maleadolescents in Bucaramanga, Colombia, from its perception with respect to services for sexual and reproductive health(SRH). Methodology: qualitative ethnographic study, using astrategy of discussion groups. We used informal discussions,interviews and focal point. Was selected by a conveniencesample of male adolescents in Bucaramanga, 2-6 strata, frompublic and private institutions, and school, between 13 and 18years, with a total of 52 participants and 7 focus groups.Results: Despite the cultural and socioeconomic differences,young people are consistent in their perceptions, needs andexpectations about sexuality and SRH services. The finalanalysis showed four categories: service experiences SSR, SSR ideal services, pornography and sexuality. Conclusions:It is apparent invisibility of the SSR and the perception ofunfavorable, from the experience of those who know her.Nevertheless, adolescents need to consider this type of service.This research leads to reflection on the ignorance of youngboys from their being, their feelings and their wish to be.